Influencing Factor to Use E-hailing Transport for Motorcycle Mode - Ismail, Nurhasyima; Kamarudin Ambak (Recent Trends in Civil Engineering and Built Environment, 2021)
The increase in population in an area also led to an increase in transport demand. In Malaysia, transport such as the e-Hailing service is gaining ground in the community and is an important mode of connecting people. This study aims to determine the level of consumer acceptance of the idea of implementing e-Hailing motorcycles. The objective of this study is to identify factors that contributes and influence users to use e-Hailing services. The study area is in urban and sub-urban areas, such as at Batu Pahat and Johor Baharu. The questionnaire was conducted and distributed among 200 respondents in the study area. The questionnaire was designed on the Technology Acceptance Model (TAM). The Correlation analysis were used in this study analysis. The results of this study shows that the relationship between variable in technology acceptance model, perceived ease of use and perceived usefulness strongly correlated and there strong relationship between these two variables. Among the suggestions to improve the use of motorcycle services among e-hailing users is that the management company must ensure that their riders are always prudent when sending passengers to their destination safely.